ANALISIS BUTIR SOAL DENGAN PENDEKATAN CLASSICAL TEST THEORY DAN ITEM RESPONSE THEORY - Mistiani, Wiwin (Paedagogia: Jurnal Pendidikan, 2016)
The test is one of the easiest and most inexpensive ways that can be done to take pictures of students' progress in the cognitive domain. Therefore, the existence of a quality test device is a necessity so that the students' cognitive abilities may be disclosed. The quality of a test device can be seen to perform qualitative and quantitative analysis. Qualitative analysis is an analysis that is performed before the tests given to participants to test their compatibility with aspects of material, construction and language, while the quantitative analysis can be done by using classical test theory and item response theory.